2018
DOI: 10.1016/j.gexplo.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acid mine drainage with biota in the Allchar Carlin-type As-Tl-Sb-Au deposit, Macedonia

Abstract: Allchar ore deposit, a well-known polymetallic mineralisation, is drained by the Majdanska River characterized by elevated concentrations of heavy metals and metalloids, particularly As, Tl and Sb. The present study was conducted at the spot of the confluence of spring water, heavily loaded with toxic metals, which joins the Majdanska River by a few meters short stream. The spring water is outflow of underground water drained by passage through polymetallic mineralisation. The chemical characteristics of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Furthermore, in the Macedonian Maidanska River, the bioconcentration and biomineralisation of Cu, As, Cr, Se, and Cs were observed in Audouinella sp, while the high bioaccumulation of Ba (3 mg/g) and intracellular biomineralisation were evidenced in Spirogyra sp. thereby positioning these algal species as a biological pathfinder for acid-mine drainage deposits (Bermanec et al 2018 ). Water and sediment chemistry, including nutrient and metal pollutants, largely influence the stream algal community composition.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Furthermore, in the Macedonian Maidanska River, the bioconcentration and biomineralisation of Cu, As, Cr, Se, and Cs were observed in Audouinella sp, while the high bioaccumulation of Ba (3 mg/g) and intracellular biomineralisation were evidenced in Spirogyra sp. thereby positioning these algal species as a biological pathfinder for acid-mine drainage deposits (Bermanec et al 2018 ). Water and sediment chemistry, including nutrient and metal pollutants, largely influence the stream algal community composition.…”
Section: Methodological Approachmentioning
confidence: 99%
“…For example, Spirogyra sp. is a benthic freshwater green algae widely distributed throughout the world (Lee and Chang, 2011) and already recognised as potential absorbent for heavy metals from mine or waste water (Bermanec et al, 2018). In addition, due to its sensitivity to the presence of pollutants such as heavy metals in water, it has also been studied to some extent for the screening of heavy metals in aquatic ecosystems (Wan Jusoh et al, 2020), particularly where point source of pollution exists (Rai et al, 2008).…”
Section: Evaluation Of Spirogyra Sp As a Bioindicator Of Heavy Metal ...mentioning
confidence: 99%
“…for different metals have been reported by other authors as well (Rajfur and K³os, 2015). For example, Bermanec et al (2018) found that Cd, Co, Sr, and Zn preferentially accumulated in Spirogyra sp. taken from the acid mine drainage impacted Majdanska River, suggesting that this algae species have great ability to accumulate metals from the aquatic environment.…”
mentioning
confidence: 99%
“…The secondary sulfate minerals in thallium deposits, including thallium sulfate and Fe-and Al-hydroxysulfate minerals, have been documented in the literature [19,[68][69][70]. As oxidation/weathering of pyrite releases large amounts of Fe 2+ and SO 4 2− into the AMD, the melanterite group dominates the secondary sulfate with less occurrence of monovalent metal sulfates (e.g., lanmuchangite and alum), other divalent metal sulfates (e.g., gypsum and epsomite), and trivalent metal sulfates (e.g., alunogen and coquimbite).…”
Section: Secondary Sulfate Mineralogy In Tl Mineralization Areasmentioning
confidence: 99%